1992
DOI: 10.1080/00071669208417511
|View full text |Cite
|
Sign up to set email alerts
|

Responses of broiler chickens to high‐frequency and low‐frequency fluorescent light

Abstract: 1. The influence of the flicker frequency on physical activity and energy expenditure of broilers was studied using commercially available high-frequency (HF) and low-frequency (LF) fluorescent lamps in a 23L:1D lighting schedule. 2. Broilers were reared under and adapted to HF. They were alternately subjected to HF and LF during measurement of activity and energy expenditure. 3. In comparison with HF, LF inhibited activity (number and intensity of movements), but did not influence energy expenditure. 4. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…As there was a trend for activity to increase by the second day in both treatments, higher activity may show that the birds are more settled. These results mirror those of Boshouwers and Nicaise (1992), who found that broilers were less active under LF than HF. Also, basal corticosterone was higher in birds kept under LF, an increase in hypothalamicpituitary-adrenal activity that occurred even though the birds were less active.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As there was a trend for activity to increase by the second day in both treatments, higher activity may show that the birds are more settled. These results mirror those of Boshouwers and Nicaise (1992), who found that broilers were less active under LF than HF. Also, basal corticosterone was higher in birds kept under LF, an increase in hypothalamicpituitary-adrenal activity that occurred even though the birds were less active.…”
Section: Discussionsupporting
confidence: 91%
“…However, from a welfare perspective, frequencies above those that are perceptible can cause adverse effects in humans (Wilkins, 1995); the same may be true of poultry, as LF has been found to inhibit activity, but without reducing energy expenditure, in broilers (Boshouwers and Nicaise, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…This 'stroboscopic' effect is even more pronounced with dimmed fluorescent light. Increased activity has been observed in birds given high frequency fluorescent light compared with low frequency fluorescent light (Boshouwers and Nicaise, 1992). Moreover, it is suspected that this stroboscopic effect is inconvenient for birds and, although not necessarily adversely affecting performance, may deleteriously affect their welfare.…”
Section: Light Sourcementioning
confidence: 99%
“…The 20 colour and source of artificial light can also affect activity; low-frequency fluorescent lighting lowers activity compared with high-frequency (Boshouwers and Nicaise, 1992) and activity is higher in red than in blue light both at the same intensity, and at higher intensities (Prayitno et al, 1997). Gait abnormalities were also reduced with red light.…”
mentioning
confidence: 99%